From Clinics to Communities: Understanding Public Perceptions of Dental Services in Pakistan - Kamran Ali; Daniel Zahra; Ulfat Bashir; Hina Zafar Raja; Asmaa Alkhtib; Minahil Arujj Younas; Ummara Manzoor; Asma Shakoor; Mariya Khalid; Amna Mansoor; Saman Hakeem; Maryam Mumtaz; et al. (Health Expectations, 2025)
ABSTRACT Introduction Access to dental services is a core component of public healthcare. The aim of this study was to evaluate the perceptions and experiences of the public regarding access, quality and affordability of dental services in Pakistan. Methods It was an analytical cross‐sectional study based on an online survey. The data collection instrument was based on eight items related to participant perceptions and experiences of dental services in public and private sectors. Pretesting of the survey questionnaire was done, and the target participants were approached through social media, and dental service providers. Results A total of 1007 participants representing all provinces of the country responded to the study questionnaire including 54.32% (n = 547) females and 45.68% (n = 460) males. Education and financial status showed the largest effect on perceptions. Although all groups agreed that dental professionals contribute positively to improving public health, those in the ‘No Education’ or ‘Poor’ groups showed fewer positive perceptions about the accessibility, quality, and affordability of dental services. Perceptions of dental services between genders showed minimal differences. Chi‐squared tests of association showed significant (p < 0.001) relationships between personal awareness of oral health and respondent characteristics such as education, employment, financial status and location. Conclusions This study provides useful insights into the public perceptions and experiences of dental health services in Pakistan. The findings reveal disparities in access, quality, and affordability of dental services among disadvantaged groups, particularly within the public sector. Oral health awareness was also reported to be low amongst people with low educational and financial status. Given the limitations of the current study, further research using qualitative methods may provide a more in‐depth understanding of the facilitators and barriers to dental services to inform a major reform to improve public dental services in the country. Patient and Public Involvement and Engagement (PPIE) Members of the public with previous experience of using dental services were involved in pretesting of the study questionnaire Pretesting of the survey questionnaire was done in two phases: In the first phase, cognitive interviews were conducted with eight members of the public including four participants each with proficiency in English and Urdu. The purpose of the cognitive interviews was to determine that the participants were able to comprehend all items of the questionnaire accurately. In the second phase the questionnaire was piloted with 15 members of the public who were given a choice to answer the questionnaire in English or Urdu based on their individual preference.